Crisis of Identity and Mimicry in Orwells Burmese Days Seen through a Local Native Character U Po Kyin: A Postcolonial Readin - B. Endo Gauh Perdana; Elisa Dwi Wardani (Journal of Language and Literature, 2017)
This study analyzes how crisis of identity and mimicry occurs in the postcolonial discourse. A local native character whose name is U Po Kyin is the focus of the study. As a native character, he holds a high ranking position for local in the British Raj in Burma. However, he is portrayed as a corrupt official as he accepts bribes and denounces his rival. His ambition to get the membership, an elite European Club, drives him infuriated to destroy his rivals reputation because naturally it is him who would be elected as the first local member of the Club. At the end of the novel, Kyin finally secures his membership but he fails to atone his evil-doings by building pagodas as a Buddhist. Kyins attitude is seen as how he manages to deal with his inferiority towards the British. He is also observed to mimic the British as his strategy to erase the idea of being colonized.There are two problem formulations in this study. The first is to find out how U Po Kyin suffers from crisis of identity through his characterization in the novel. Then, the second objective is to understand how his crisis of identity leads him to mimic the British.This study condludes that U Po Kyin suffers from crisis of identity. He is oppressed conscious and unconsciously by the British. This causes his self-image to be eroded. Even though he is relatively wealthier than his fellow natives, he still craves for more as he realizes that there is something more than money. He wants to be detached from his inferiority. The elite European Club represents his ambition because it offers him status to be like the British. That is why he schemes to crush his rival. In his schemes, denigrating his rival means to mimic the British because he needs to differ himself from the natives. However, he is still powerless because the British still consider him as the subject of colonialization. Keywords: crisis of identity, mimicry, postcolonial reading